Reinterpretasi Makna Minyak Urapan - Otta, Pieter (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
This article is written with the aim of exploring the meaning of anointing oil found in Exodus 30:30-31, as well as to answer some of the following questions : Does the use of the word ‘anointing oil’ in the present days is in an appropriate and biblical context? Does the use of anointing oil, where there are certain groups who use it as a tool to heal the sick, bless a new car, bless a new house, etc. accordance with this context? Does the use of the word ‘anoint’ in James 5:14 have the same meaning as ‘anointing oil’ in Exodus 30:30-31? This study was conducted through a literature review by synthesizing some biblibcal verse excavations to find the true meaning. The result is in the conceptual thought that the context of Exodus 30:30-31, which discusses how to make anointing oil from myrrh, sweet cinnamon, fragrant cane, cassia and olive oil, is intended to anoint the king, priest, the tabernacle and its utensils; it is different from the meaning of anointing oil which is rife in the church today. The thesis of this article is that the meaning and understandingin Exodus 30:23-31 is different from the phrase “anointing him with oil” in James 5:14.